Teacher Emotion Inventory: validation in a sample of Spanish teachers - Rodríguez-Donaire, Alba; Luna, Pablo; Pérez-González, Juan-Carlos; Cejudo, Javier (Anales de Psicología / Annals of Psychology, 2024)
Background: The Teacher Emotion Inventory (TEI) scale is an instrument that evaluates discrete emotions experienced by teachers in the teaching-learning process. The aim of this study was to examine the psychometric properties of the brief Spanish version of the Teacher Emotion Inventory scale (TEI-BSV) using a sample of 567 teachers (65.5% women), aged between 25 and 65 years (M = 46.04; SD = 9.09). Methods: After adaptation through back-translation, the teachers completed a battery of tests included in the TEI-BSV: an emotional intelligence questionnaire, two subjective well-being scales, a burnout scale and a scale on engagement. Results: The data revealed adequate internal consistency of the TEI-BSV subscales, and exploratory and confirmatory factor analyses provided evidence that the TEI-BSV has a four-factor structure with good adjustment, as opposed to the original five-factor structure proposed. There was evidence of convergent validity of the TEI-BSV, as well as criterion and incremental validity. Conclusions: The TEI-BSV could be a useful instrument for the ecological assessment of teachers' discrete emotions in the context of their workplace.